Gender Relation in Tea Plucking Workers: A Case Study of Gender Division of Labour and Gender Relation in Gambung Tea Plantation, West Java - Sita, Kralawi; Herawati, Erna (Sodality: Jurnal Sosiologi Pedesaan, 2017)
ABSTRACTMen and women’s participation in tea plucking have been divided based on gender and strongly patriarchy-influenced. This division of labor cause a gender relation describes specific case of their relations in tea plantation. This study aims to describe the gender relation among the tea plucking workers at Gambung Tea Plantation, analyzed by qualitative approach, particularly treated as a case study. Data collected by in-depth interviews, observation, focus group discussion, and documentation. It was triangulated and analyzed using Harvard Analytical Framework and Gender Balance Tree in Gender Action Learning System approaches. The result shows that both men and women have equal access employment in plucking tea but their participation divided based on gender and patriarchy-influenced. Women have large participation in manual job description while men dominates on mechanic. Manual labor requires longer working-hour. It cause women have longer on working-hour than men. It is also enhance their burdern, eventhough generally they have double roles. As the consequences, women must work harder on their both roles. However, women’s participation in productive works enable women to generate income that makes them gaining better position within the household, such as a decision maker. It makes them able to access skill capacity.Keywords: gender relation, tea pluckeig worker, tea plantation, Harvard Analytical Framework, Gender Action Learning SystemABSTRAKPartisipasi laki-laki dan perempuan dalam pemetikan teh dibagi berdasarkan gender dan dipengaruhi kuat oleh patriarki. Pembagian kerja ini menimbulkan relasi gender yang menggambarkan kasus tertentu hubungan laki-laki dan perempuan di perkebunan teh. Penelitian ini bertujuan untuk mendeskripsikan relasi gender pada kegiatan pemetikan teh di Perkebunan Teh Gambung, dengan pendekatan kualitatif, dalam studi kasus tertentu. Pengumpulan data dilakukan dengan metode wawancara mendalam, observasi, diskusi grup terpusat, dan dokumentasi. Data ditriangulasi dan dianalisis menggunakan Harvard Analytical Framework dan Gender Balance Tree dalam Gender Action Learning System. Hasil penelitian menunjukkan bahwa baik laki-laki dan perempuan mempunyai akses yang sama dalam pemetikan tetapi partisipasi mereka dibagi berdasarkan gender dan dipengaruhi patriarki. Perempuan mempunyai partisipasi besar dalam pemetikan manual sedangkan laki-laki mendominasi mekanisasi mesin petik. Manual membutuhkan waktu yang tinggi yang menyebabkan perempuan mempunyai waktu kerja yang lebih banyak dari laki-laki dan hal ini menambah beban perempuan yang secara general mempunyai beban ganda. Sebagai konsekuensinya, perempuan harus bekerja lebih keras. Namun, partisipasi perempuan dalam pekerjaan produktif memungkinkan perempuan untuk menghasilkan pendapatan yang memberikan perempuan posisi yang lebih baik dalam rumah tangga, seperti kekuasaan dalam pengambilan keputusan dan posisi tawar dalam mengakses peningkatan kapasitas keterampilan.Kata kunci: relasi gender, pemetik teh, perkebunan teh, Harvard Analytical Framework, Gender Action Learning System